Healthy eating away-from-home: effects of dining occasion and the number of menu items - Boo, Huey Chern; Chan, L. T.; Ungku Zainal Abidin, Ungku Fatimah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
Consumers are reported to be increasingly concerned about their health. Nonetheless, consumers show different attitudes toward food at home and away from home. In particular, consumers tend to shy away from healthy food items when dining on special occasions. This study is the first to look into the number of healthy menu items provided to consumers during dining occasions. The impacts of two independent variables (dining occasion: normal vs. special; number of healthy items: limited vs. extended) on consumers’ dining menu selection was examined among female university students. The results of this study indicate that both dining occasion and the number of healthy items offered could influence consumers’ food selection independently. Although consumers are more likely to choose unhealthy items while dining’on special occasions, offering more healthy items would increase the probability of healthy eating. This study also offers some insights into the food categories and cooking methods favored by consumers. Further studies should explore other potential foods that would enhance the selection of healthy options by consumers.